Inter-region Economic Analysis to Improve Economic Development Maritime In North Maluku Province - Musdar Muhammd; Devanto Shasta Pratomo; Wildan Syafitri (Universitas Negeri Malang, 2017)
The main purpose of this research to analysis sector and sub-sector development of chartered investment counsel maritime between regions which is bases sector in sub-province and opportunity of job activity at sub-sector fishery of sub-province in North Maluku with observation PDRB sub-province/town during five years (2009-2013). Then, analyses development policy strategy of chartered investment counsel maritime North Maluku. By using technique analyses LQ, multiplier effect, and AHP. The result of analysis shows sub-province Halmahera South and second archipelago Sula of the sub-province that there is sector and sub-sector bases which at most when in comparing to sector and sub-sector bases there is sub-province/town province North Maluku, multiplier effect opportunity of job activity at sub-sector fishery happened in the year 2010 that there is in sub-province/city West Halmahera, South-east Halmahera, East Halmahera North Halmahera, and city of Tidore archipelago’s. In the year of 2013, multiplier effect sub-sector fishery catches there is at sub-province West Halmahera, South Halmahera, and the city of Tidore archipelagoes. Development policy strategy of chartered investment counsel maritime human resource, public service, natural resources with fishery & oceanic requirement in making a preference for development of chartered investment counsel maritime of North Maluku.Keywords: Economic Between Regions, Pre-Eminent Sector, Development Economic MaritimJEL Classification: O18, R11